Implementation of Safety Policy at PJL 75 by the Jombang Regency Transportation Office - Fauziah, Siti Nur; Muljanto, Muhammad Agus (Journal La Sociale, 2024)
The train is a land transportation that is widely used by some Indonesian people. With the many benefits of trains, the community is expected to provide awareness in the importance of giving way when trains will pass. This needs to be done because the load carried by the train is very heavy and also the train carriages are also long, making it difficult if the train is forced to brake suddenly. Therefore, the importance of public awareness when crossing the tracks to remain careful and obey traffic signs. The purpose of this study is to determine and analyze the implementation of road user safety policies at level railway crossings in Brambang village by the Jombang Regency Transportation Agency. This type of research is a type of case study research and the method used in this research is a qualitative method. The author uses Miles and Huberman's data analysis technique. The results of this study based on the theory of policy implementation from Charles O. Jones show that the division of labor that has been formed by the Jombang Regency Transportation Office is organized, the lack of knowledge of PJL at the crossing about safety and security at level crossings and the Jombang Regency Transportation Office has carried out its duties such as providing field evaluations. The conclusion of this study is that the implementation of safety and security policies at JPL 75 is in accordance with the theory of policy implementation from Charles O. Jones, but there are still many shortcomings in the policy implementation process.